Sports-Related Injuries in New Zealand: National Insurance (Accident Compensation Corporation) Claims for Five Sporting Codes From 2012 to 2016 - King, D; Hume, P; Hardaker, N; Cummins, C; Gissane, C; Clark, T (BMJ Publishing, 2019)
Objectives: To provide epidemiological data and related costs for sport-related injuries of five sporting codes (cricket, netball, rugby league, rugby union and football) in New Zealand for moderate-to-serious and serious injury claims. Methods: A retrospective analytical review using detailed descriptive epidemiological data obtained from the Accident Compensation Corporation (ACC) for 2012-2016. Results: Over the 5 years of study data, rugby union recorded the most moderate-to-serious injury entitlement claims (25 226) and costs (New Zealand dollars (NZD$)267 359 440 (£139 084 749)) resulting in the highest mean cost (NZD$10 484 (£5454)) per moderate-to-serious injury entitlement claim. Rugby union recorded more serious injury entitlement claims (n=454) than cricket (t(4)='66.6; P<0.0001); netball (t(4)='45.1; P<0.0001); rugby league (t(4)='61.4; P<0.0001) and football (t(4)=66.6; P<0.0001) for 2012-2016. There was a twofold increase in the number of female moderate-to-serious injury entitlement claims for football (RR 2.6 (95%CI 2.2 to 2.9); P<0.0001) compared with cricket, and a threefold increase when compared with rugby union (risk ratio (RR) 3.1 (95%CI 2.9 to 3.3); P<0.0001). Moderate-to-serious concussion claims increased between 2012 and 2016 for netball (RR 3.7 (95%CI 1.9 to 7.1); P<0.0001), rugby union (RR 2.0 (95% CI 1.6 to 2.4); P<0.0001) and football (RR 2.3 (95%CI 1.6 to 3.2); P<0.0001). Nearly a quarter of moderate-to-serious entitlement claims (23%) and costs (24%) were to participants aged 35 years or older. Conclusions: Rugby union and rugby league have the highest total number and costs associated with injury. Accurate sport exposure data are needed to enable injury risk calculations.